A Multi-Material Flame-Retarding System Based on Expandable Graphite for Glass-Fiber-Reinforced PA6 - Tomiak, Florian; Zitzmann, Melanie; Drummer, Dietmar (Polymers, 2023)
A synergistic multi-material flame retardant system based on expandable graphite (EG), aluminum diethylphosphinate (AlPi), melamine polyphosphate (MPP), and montmorillonite (MMT) has been studied in glass-fiber-reinforced polyamide 6 (PA6). Analytical evaluations and fire performances were evaluated using coupled thermogravimetric analysis (TGA) and Fourier-transform infrared spectroscopy (FTIR) as well as cone calorimetry, UL-94 fire testing, and limiting oxygen index (LOI). A combination of EG/AlPi/MPP/MMT has been shown to provide superior flame-retarding properties when integrated at 20 wt.% into glass-fiber-reinforced PA6 (25 wt.%), achieving UL-94 V0 classification and an oxygen index of 32%. Strong residue formation resulted in low heat development overall, with a peak heat release rate (pHRR) of 103 kW/m2, a maximum of average heat release rate (MAHRE) of 33 kW/m2, and deficient total smoke production (TSP) of 3.8 m2. Particularly remarkable was the structural stability of the char residue. The char residue could easily withstand an areal weight of 35 g/cm2, showing no visible deformation.
CRIS-Team Scopus Importer:2023-11-10
Keywords: aluminum diethylphosphinate; expandable graphite; flame retardancy; melamine polyphosphate; montmorillonite; PA6